Macroeconomic determinants that influencing inflation rate in Malaysia / Syazanisa Zaini - Zaini, Syazanisa (Faculty of Business and Management, 2016)
The aim of this study is to investigate the relationship between selected macroeconomic determinants with inflation rate in Malaysia. The study used 3 models of Single Linear Regression in order to find the relationship between money supply, unemployment rate and exchange rate with inflation rate. The quarterly data was collected from 2000 until 2014. From the result, it reveals that money supply has positive significant relationship toward inflation rate while unemployment rate and exchange rate have negative significant relationship towards inflation rate. It means that there are effects between money supply, unemployment rate and exchange rate with inflation rate. These results further our understanding of the relationship between money supply, unemployment rate and exchange rate with inflation rate thus this study should be useful for public, industries and policy makers.